Cost accounting and digital health technology adoption: impacts on hospital efficiency and patient care - Salomi Jacomina Hehanussa (Jurnal Konseling dan Pendidikan, 2025)
Digital health technologies (DHTs) are revolutionizing healthcare by enhancing patient outcomes and operational efficiency in hospitals. However, the adoption of these technologies involves significant financial investments and raises questions regarding their cost-effectiveness. This study examines the role of cost accounting in evaluating and supporting the adoption of digital health technologies in hospitals, exploring how accurate cost assessment can influence decision-making, resource allocation, and overall hospital efficiency. Through a mixed-methods approach, combining quantitative analysis of hospital financial data and qualitative interviews with hospital administrators, this research identifies key cost factors associated with DHT adoption, including capital expenditure, operational costs, and indirect benefits like patient care improvement. Findings show that hospitals employing comprehensive cost accounting methods are better positioned to make informed decisions regarding DHT investments, leading to improved patient care and streamlined operations. The paper also discusses challenges such as the initial financial burden and integration complexities that hospitals face when adopting digital health solutions. Policy implications for optimizing cost accounting practices to support technology adoption in healthcare are discussed.